Penggunaan Bahasa Formal dan Informal pada Organisasi Himpunan Mahasiswa Islam (HMI) FIS Unimed - Mhiranda Theresia Sitorus; Muhammad Izhar Tumanggor; Samiullah Putra Limbong; Suci Rohani Panjaitan; Nurul Azizah (Jurnal Bintang Pendidikan Indonesia, 2025)
This study aims to examine the use of formal and informal language in communication in the Islamic Student Association (HMI) FIS Unimed, as well as the factors that influence and its impact. With a descriptive qualitative approach, data were obtained through in-depth interviews with active members. The findings of the study indicate that formal language is chosen in meetings and official events to create a professional atmosphere, while informal language is more often used in daily interactions to strengthen relationships between members. The choice of language type is influenced by the context of the situation, relationships between individuals, and communication goals. However, there are challenges for some members who have difficulty distinguishing when to use formal language in official events and when to use informal language in casual situations. The use of balanced formal and informal language is very important to achieve effective communication and strengthen solidarity among members. Therefore, it is recommended that there be further socialization and mentoring so that members can better understand and apply the communication norms that apply in the organization. Keywords: